Główne tematy teologiczne Drugiego Listu św. Piotra - Mickiewicz, Franciszek (Collectanea Theologica, 2018)
The author of the Second Letter of St Peter wrote at a time when there were false prophets and teachers among Christians, whose erroneous learning seemed very attractive to many, and therefore became a serious threat to the young Church. Because of their strong influence and the danger that many who were unstable in faith and morals would follow their example, Peter sharply denounced their teaching and scandalous conduct. Above all, however, he wrote his letter to remind Christians of the apostolic teachings they once gave them. This article presents the main theological topics that are the content of the teaching of the author of the Second Letter of St Peter: the divine authority of Jesus Christ (Christology), the salvific will of God and Jesus Christ (soteriology), the promise of the Lord’s second coming (eschatology), the authority of the Holy Scriptures and its proper interpretation, and moral life based on the Gospel.